Analisis Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Bahan Baku Bungkil Kedelai pada Industri Pakan Ternak di Indonesia - Aritonang, Paraden Arianto; Daryanto, Arief; Hendrawan, Dudi S. (Universitas Brawijaya, Indonesia, 2015)
In the livestock feed industry, raw material is a crucial component. Soybean Mealis one of the main raw materials for the manufacture of animal feed making instead of corn.Viewed from the imported needs by the feed industry, and also the potential in future growthof this industry, the trading firms engaged in feed raw materials; particularly soybean mealis trying to enter and consolidate its position in the Indonesian market, This condition led tothe rigorous competition. The purpose of this study is analyzing the relationship between thefactors of the marketing mix with purchasing decisions of soybean meal and analyzing theimportance and performance attributes of marketing mix factor in and livestock feed industryin Indonesia. Methods which are used in collecting the data by giving questionnaires for25 respondents from 25 feed mills listed in association GPMT. The processing and dataanalysis using Multiple Linear Regression and Importance Performance Analysis (IPA) inorder to assessing each attribute of the marketing mix. The result showed that from sixvariables of marketing mix, price variable and place variable has a significant influence onthe soybean meal purchasing decisions. Based on the results of IPA at prices variable, term ofpayment and the interest rate offered for payment are must be prioritized. While the results ofthe IPA at place variable, the ability of sellers to offer soybean meal from different sources invarious countries of origin, the ability of sellers offering soybean meal to the port of Belawan,the ability of sellers offering soybean meal to the port of Semarang and ownership of storagefacilities must be prioritized.